Analysis of Self-Efficacy in Mathematics Learning for Students - Sihite, Reena Dwi Rizki; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
Self-efficacy is a strong influence that shows students' self-confidence, where the effectiveness of self-efficacy in elementary school students in solving problems in mathematics learning can be seen from the results obtained when self-efficacy is good. This research aims to analyze the level of self-confidence or confidence of students regarding the abilities they have in terms of learning mathematics. The results of the analysis in this study show that there are students with several criteria that are produced, namely, how much the students consider the level of difficulty of the task being faced by the students, the sense of ability that students have when dealing with mathematical problems and knowing how much students feel confident. himself with his abilities. The results of the analysis in this study show how much self-confidence students have as explained in the results section of this study when faced with mathematical problems, students will not easily give up or avoid tasks given by the teacher if they have tried hard and the task is difficult to complete. completed, then they may give up if the task is too difficult.